PERANCANGAN PROTEKSI ARUS PAKSA PADA PIPA BAJA API 5L DENGAN COATING DAN TANPA COATING DI DALAM TANAH - Tubagus Noor R; Sulistijono Sulistijono; Azmi Mahiri; M. Rizal Pambudi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Impressed Current Cathodic Protection (ICCP) is a metal protection system from corrosion using DC current source from outside the system. The positive pole of DC current source is connected to the inert anode while the negative pole of the DC current source connected with metal or cathode to be protected from corrosion attack. ICCP has several advantages such as easy to control the flow of protection, is easy to detect damage to the protection system, and can be used in various types of cathodes and a different environment, and others. Research (Tito, 2002) mentions the advantages of the ICCP system is that it can be designed for applications with a high degree of flexibility because they have wide range of current output capacity. It’s means that current demand can be set either manually or automatically by changing the output voltage in accordance with the needs, another advantage of this system can protect an area that is large enough. The studies regarding the ICCP is progressing towards design in tune with the cathode and the environment, this is due to the cathode and a certain kind of environment will require different designs. This research is designed ICCP on the cathode API 5L grade B with different coatings in different soil moisture conditions. At the cathode with different coating thicknesses showed that the thicker the coating, the current required protection will decrease, while the environmental conditions with different humidity, the higher the soil moisture, the resulting flow needs protection also increased Keywords: corrosion, cathodic protection, impressed current, API 5L.